Meningkatkan Kemampuan Guru Dalam Melaksanakan Penilaian Proses Pembelajaran Melalui Supervisi Klinis Pada SD Negeri 1 Padangkerta - Ni Ketut Suarni (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to improve the ability of teachers to carry out assessments through clinical supervision at SD Negeri 1 Padangkerta. In the assessment of the learning process in the classroom, there are several important factors that need to be known, namely: 1. Definition of Assessment, 2. Concept of Assessment, 3. Principles of assessment, 4. Assessment techniques, and 5. Assessment steps. The definition of supervision cannot be interpreted narrowly as a process to supervise and attempt to improve limited teaching in the classroom, but wider than that. Supervision of educational units is a direct function of education management while classroom supervision or field of study is specifically focused on the teaching and learning process. Clinical supervision is a face-to-face process between the supervisor and the teacher, who talks about teaching and what has to do with it. Data was collected through analysis of statistical data. In carrying out classroom-based assessments, teachers at SD Negeri 1 Padangkerta, Semester I of the Academic Year 2016/2017. This can be proven from the final calculation results obtained is 84.4. Based on the analysis and discussion as described above, it was found that there had been an increase in the activity of participants in the assessment of the learning process in the classroom for teachers at SD Negeri 1 Padangkerta. Finally it can be concluded that there is a significant influence with efforts to improve the ability of teachers to carry out the assessment of the learning process through clinical supervision in SD Negeri 1 Padangkerta, as evidenced by the initial results of 66.3 and the final results after clinical supervision are: 84.4